Professional networks and their coevolution with executive careers: Evidence from North America and Europe - Nicoletta Berardi; Marie Lalanne; Paul Seabright (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper examines how networks of professional contacts contribute to the development of the careers of executives of North American and European companies. We build a dynamic model of career progression in which career moves may both depend upon existing networks and contribute to the development of future networks. We test the theory on an original dataset of nearly 73 000 executives in over 10 000 firms. In principle professional networks could be relevant both because they are rewarded by the employer and because they facilitate job mobility. Our econometric analysis suggests that, although there is a substantial positive correlation between network size and executive compensation, with an elasticity of around 20%, almost all of this is due to unobserved individual characteristics. The true causal impact of networks on compensation is closer to an elasticity of 1 or 2% on average, all of this due to enhanced probability of moving to a higher-paid job. And there appear to be strongly diminishing returns to network size.
urn:nbn:de:hebis:30:3-487660
Keywords: D85; J31; J62; M12; 330; professional networks; labor mobility; executive compensation